HUBUNGAN PEMBERIAN REWARD TERHADAP MOTIVASI KERJA PERAWAT DI RUMAH SAKIT UMUM DAERAH DR. RM. DJOELHAM BINJAI TAHUN 2021 - Juliati Juliati; Aisyah Aisyah (Universitas Pahlawan Tuanku Tambusai, 2022)
Reward is an appreciation that is given in the form of material or speech, either individually or as an institution for a certain appreciation. Work motivation is something that creates enthusiasm and encouragement to work. This type of research is a descriptive study using a cross-sectional analytic study design. The purpose of this research is to determine the relationship between reward giving and work motivation of nurses at the Dr. General Hospital. RM. Djoelham Binjai in 2021. In this study, the sampling technique was carried out by taking 20% ​​of the total population of 200. So the sample in this study was 40 people. The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 1, the results are p.value = 0.000 at df = 1 where sig < (0.000< 0.05) then H0 is rejected so it can be concluded that there is a relationship between reward giving and work motivation of nurses at the Dr. RM. Djoelham Binjai in 2021. The results of this study are expected to provide input to the hospital management to further improve the provision of rewards in order to increase work motivation. Keywords: Reward, Work Motivation